Infection of a β-galactosidase-deficient mouse strain with Theiler’s murine encephalomyelitis virus reveals limited immunological dysregulations in this lysosomal storage disease - Wannemacher, Rouven; Stegmann, Felix; Eikelberg, Deborah; Bühler, Melanie; Li, Dandan; Kohale, Sayali Kalidas; Asawapattanakul, Thanaporn; Ebbecke, Tim; Raulf, Marie-Kristin; Baumgärtner, Wolfgang; Lepenies, Bernd; Gerhauser, Ingo (Frontiers in Immunology, 2025)
IntroductionA hallmark of many lysosomal storage diseases (LSD) is the alteration of immune responses, often starting before the onset of clinical disease. The present study aimed to investigate how GM1 gangliosidosis impacted the course of an acute central nervous system (CNS) virus infection before the clinical onset of LSD.MethodsFor this purpose, Glb1-/- and wildtype control mice (both C57BL/6 background) were intracerebrally infected with the BeAn strain of Theiler’s murine encephalomyelitis virus (TMEV) at the age of 5 weeks and sacrificed 4, 7, 14 and 98 days post infection, respectively. Histology, immunohistochemistry, and flow cytometry was used to assess viral load and immune cell activation and infiltration.ResultsBoth wildtype and Glb1-/- mice were able to clear the virus from the CNS and did not develop any clinical symptoms of TMEV-associated disease, thus indicating no overt alteration in susceptibility to TMEV infection. However, in the early phase post infection, Glb1-/- mice displayed a slightly delayed T cell response as well as an increase in the number and activation of CNS microglia.DiscussionThese results suggest that already in the early stage of disease (before clinical onset) GM1 gangliosidosis causes an impaired T cell response and microglial hyperreactivity.